Conflict Management Counseling For Community Leaders In West Kaduara Village After Village Head Election - Annisa Izzah Dinillah; Abelda Fauzia Sasabela; Ahmad Nizar; A. Syaiful Islam (Politeknik Siber Cerdika Internasional, 2023)
The existence of social conflict in the election of village heads affects all aspects of people's daily life which as a whole has an impact on social relations between communities. Family values and blood relations have faded and are very concerning. Knowing conflict management after the election of Kaduara Barat Village Head. The research method is the method used by researchers in collecting research data, such as interviews, observations, tests and documentation (Arikunto, S. 2002). The method used in this research is qualitative method. The following is an overview of indicators of conflict resolution carried out by the village head and community leaders to resolve and handle village head election conflicts in Kaduara Barat Village. Persuasion first, accommodation second, compromise third. When the Village Head Election goes smoothly and in an orderly manner, it results in an elected village head. Every candidate and his supporters must respect and honor the outcome of the decision. If there is a conflict between a candidate and his supporters, then the conflict is limited to a debate of ideas and opinions, not blind fanaticism and occurs before the election. After the election life returned to normal.